Organized Crime in Europe - Koslowski, Ricco (Magyar Rendészet, 2019)
The study introduces the current situation in connection with organized criminal groups in Europe. By differentiation of their specific characteristics, the activity of terrorist and organized crime groups in Europe are presented. The author provides some insight into the activity of the currently working organized crime groups through the assessment of the activity of transnational organized crime groups. In the forecast of future evolution of organized crime, the author emphasizes the importance of regular cooperation at national and international, as well as inside and outside of the competent organizations.